OPTIMASI PRODUKSI DAN IDENTIFIKASI SENYAWA ANTIMIKROB DARI JAMUR ENDOFIT Sporothrix sp LBKURCC43 TANAMAN DAHLIA (Dahlia variabilis) - - Paslun; - Saryono; Chiristine Jose (Sistem Informasi, 2016)
Dahlia tubers contain fungus Sporothrix sp which have antimicrobial activity.The objective of this research was to determine the agitation that effect the activity of antimicrobial in malt extract broth (MEB). The result showed that agitation of 150 rpm have the antimicrobial activity against Staphylococcus aureus with 21.0 mm and Escherichia colii with 12.8 mm. The identification of function group showed the extract contained O-H, C=O and Amide with UV and IR spectroscopy.